2018
DOI: 10.1007/s00011-018-1155-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Adiponectin administration alleviates DSS-induced colonic inflammation in Caco-2 cells and mice

Abstract: BackgroundAdiponectin, a protein hormone produced by adipose tissues, exhibits anti-inflammatory functions in various models. This study was investigated the effects of adiponectin on dextran sodium sulfate (DSS)-colonic injury, inflammation, apoptosis, and intestinal barrier dysfunction in Caco-2 cell and mice.Materials and methodsThe results showed that DSS caused inflammatory response and intestinal barrier dysfunction in vitro and in vivo. Adiponectin injection alleviated colonic injury and rectal bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
2
10
1
Order By: Relevance
“…In addition, infusion of osmotin using osmotic pumps attenuates dextran sodium sulfate-induced colitis in mice [58] . These effects are consistent with anti-inflammatory effects of adiponectin and AdipoRon [58][59][60] . The results from in vitro and in vivo experiments indicate that osmotin as well as adiponectin and AdipoRon could prevent inflammatory diseases.…”
Section: Anti-inflammatory Effectsupporting
confidence: 84%
“…In addition, infusion of osmotin using osmotic pumps attenuates dextran sodium sulfate-induced colitis in mice [58] . These effects are consistent with anti-inflammatory effects of adiponectin and AdipoRon [58][59][60] . The results from in vitro and in vivo experiments indicate that osmotin as well as adiponectin and AdipoRon could prevent inflammatory diseases.…”
Section: Anti-inflammatory Effectsupporting
confidence: 84%
“…57 DSSinduced colonic inflammation is commonly accompanied by apoptosis via influencing apoptosis-related proteins in response to various cellular stresses, such as inflammation and oxidative stress. 58 In addition, it has been reported that peripheral inflammation can induce neuroinflammation in the CNS via disruption of the BBB. 8 The unique characteristics of this barrier include tight intercellular junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study aimed to identify a novel target and to explore the underlying mechanisms for IBD treatment. DSS is widely adopted to stimulate colonic inflammation for in vivo and in vitro IBD models (25,26), and in a DSS mouse IBD model, DSS appears to be directly toxic to colonic epithelial cells in the basal crypt (26). Thus, in the present study, DSS was used to treat Caco-2 cells and the effects of DSS on Caco-2 cells and IBD tissues were examined.…”
Section: Discussionmentioning
confidence: 98%